Factors affecting a senior management culture change for total quality metamorphosis - Angeli, Ioannis; Jones, Jeffrey; Sabir, Bahir (My University, 1998)
A three-year joint research study focuses on the in-depth investigation of the quality parameters that are necessary to bring about change in senior management (SM) culture for improved leadership quality, as well as factors of “how” to succeed in its implementation. Analysis reveals overall agreement on the most important success factors, which are presented in this paper. This enables the development of an analytic model (one based on quantitative results and one based on qualitative results) for a CEO's culture change implementation process, required to achieve total quality metamorphosis (TQm) and SM leadership. © 1998, MCB UP Limited
Keywords: Quality function deployment; Management; Organizational; Quality